Les Quotas - Marie-Laure Schultze; Sujarei Tali (Glad!)
What you will see happens aboard a shabby spaceship, at the edge of a galaxy. The Intergalactic, the totalitarian power in place, stalks those who don’t obey to its rules. Among these rules, the obligation to engage in coitus, with a number of coitus per period fixed by the Inter. In this universe, the choice of whom you have sexual relationships with, how and at which rate doesn’t belong to you anymore.This narrative is presented in three different forms: a comic, an audio recording and a novel, three ways (graphic, audio and textual) as three attempts to thwart Kimée and Djoa’s gender and sexuality—the characters, and their universe. These three variations on the theme of the Inter are introduced by a short introduction, and followed by a “seaming text”, which genealogically recounts the creation of these three